The Effectiveness of Gentle Human Touch in Stabilizing Vital Signs of Preterm Infants with Respiratory Distress Syndrome - Sri Wahyuni; Fatma Zulaikha; Ni Wayan Wiwin Asthiningsih; Nur Fithriyanti Imamah (CV. CENDIKIA JENIUS INDONESIA, 2026)
Respiratory Distress Syndrome (RDS) is a major respiratory disorder in premature infants that frequently causes unstable vital signs and increases neonatal morbidity and mortality. Therefore, safe non-pharmacological interventions are needed to support physiological stability during intensive care. This study aimed to analyze the implementation of Gentle Human Touch (GHT) in stabilizing the vital signs of premature infants with RDS in the Neonatal Intensive Care Unit (NICU). A case study design was employed involving one premature infant diagnosed with very low birth weight and RDS. Data were collected through clinical observation, measurement of vital signs, and the Premature Infant Pain Profile-Revised (PIPP-R) before and after a 10-minute GHT intervention administered once daily for three consecutive days (December 30, 2025–January 1, 2026). Data were analyzed descriptively. The findings demonstrated decreased respiratory and heart rates, increased oxygen saturation, normal body temperature, reduced chest retractions, and improved infant calmness without increased pain. In conclusion, GHT is an effective, safe, and easily applicable non-pharmacological nursing intervention for improving the physiological stability of premature infants with RDS. Further studies involving larger sample sizes are recommended.